Enzymatic Activity Is Not Required for Phospholipase D Mediated TNF-α Regulation and Myocardial Healing - Klier, Meike; Gorressen, Simone; Urbahn, Marc-Andre; Barbosa, David; Ouwens, Margriet; Fischer, Jens W.; Elvers, Margitta (Frontiers in Physiology, 2018)
Phospholipase D1 is a regulator of tumor necrosis factor-α expression and release upon LPS-induced sepsis and following myocardial infarction. Lack of PLD1 leads to a reduced TNF-α mediated inflammatory response and to enhanced infarct size with declined cardiac function 21 days after ischemia reperfusion (I/R) injury. Deficiency of both PLD isoforms PLD1 and PLD2 as well as pharmacological inhibition of the enzymatic activity of PLD with the PLD inhibitor FIPI protected mice from arterial thrombosis and ischemic brain infarction. Here we treated mice with the PLD inhibitor FIPI to analyze if pharmacological inhibition of PLD after myocardial ischemia protects mice from cardiac damage. Inhibition of PLD with FIPI leads to reduced migration of inflammatory cells into the infarct border zone 24 hours after experimental myocardial infarction (MI) in mice, providing first evidence for immune cell migration to be dependent on the enzymatic activity of PLD. In contrast to PLD1 defi-cient mice, TNF-α plasma levels were not altered after FIPI treatment of mice. Consequently, infarct size and left ventricular function were comparable between FIPI treated and control mice 21 days post MI. Moreover, cell survival 24 hours post I/R was not altered upon FIPI treatment Our results indicate that the enzymatic activity of PLD is not responsible for PLD mediated TNF-α signaling and myocardial healing after I/R injury in mice. Furthermore, reduced TNF-α plasma levels in PLD1 deficient mice might be responsible for increased infarct size and im-paired cardiac function 21 days post MI.